2018
DOI: 10.1186/s11658-018-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces apoptosis and the formation of reactive oxygen species in rat glioma cells

Abstract: BackgroundArsenic trioxide (As2O3) has a dramatic therapeutic effect on acute promyelocytic leukemia (APL) patients. It can also cause apoptosis in various tumor cells. This study investigated whether As2O3 has an antitumor effect on glioma and explored the underlying mechanism.ResultsMTT and trypan blue assays showed that As2O3 remarkably inhibited growth of C6 and 9 L glioma cells. Cell viability decreased in glioma cells to a greater extent than in normal glia cells. The annexin V-FITC/PI and Hoechest/PI st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…This change is related to the mitochondrial damage caused by the production of intracellular ROS. However, the inhibition rate for normal rat glial cells was less than 10% of that for rat glioma cells [ 42 ].…”
Section: Arsenic Trioxide Acts Through Oxidative Damagementioning
confidence: 99%
“…This change is related to the mitochondrial damage caused by the production of intracellular ROS. However, the inhibition rate for normal rat glial cells was less than 10% of that for rat glioma cells [ 42 ].…”
Section: Arsenic Trioxide Acts Through Oxidative Damagementioning
confidence: 99%
“…9,10 Interestingly, some studies have shown that ATO could also inhibit growth and induce apoptosis in a variety of solid tumor cells, such as breast, liver, gastric, prostate, renal, bladder, and glioma cells. [10][11][12][13][14] However, several limitations hinder its applications in clinical practice. The free ATO in aqueous solution exists as arsenite ions, with fast elimination in vivo, poor pharmacokinetics, and unacceptable systemic toxicity, including peripheral neuropathies and liver failure.…”
Section: Introductionmentioning
confidence: 99%
“…The Immunohistochemical demonstration of p53 positive cells has confirmed that the main mode of NiNPs-cell death was the programmed cell death, particularly apoptosis. When the damage in the gene is too sever and couldn't be repaired by it's own cell, the induction of apoptosis by p53 is processed (Wawryk-Gawda et al, 2014).The significant increase in the number of p53 positive kidney tubular cells in the NiNPs treated rats indicates the increased apoptosis mode of cell death, while the size-dependent difference may be related to the induced oxidative stress since oxidative stress is one of the important factors that are known to induce apoptosis (Sun et al, 2018). However, the smallest NiNPs size showed higher p53 positive cells than the other two larger sizes.…”
Section: Discussionmentioning
confidence: 99%